The development of judgment and decision making in children and adolescents - Jacobs, Janis E.; Klaczynski, Paul A. (L. Erlbaum Associates, 2005)
"The purpose of this volume is to bring together the voices of several leading authors who are conducting cutting-edge research and developing new theoretical perspectives related to the development of judgment and decision making." "The Development of Judgment and Decision Making in Children and Adolescents is intended for researchers interested in decision making or developmental psychology, practitioners, or for graduate courses on decision making or cognitive or social development."--Jacket.